BIRD AND ARTHROPOD COMMUNITIES IN FRAGMENTED HABITAT OF TERNATE - Fadila Tamnge; Aqhsan Shadikin Nurdin (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Habitat loss and fragmentation affect bird communities. Edge area created by fragmentation can affect bird communities through availability of arthropod. The objectives of this study are to examine whether there is any difference in bird diversity and abundance between different plantation types and location between fragments, and to examine if there is any correlation between arthropod and birds. To record Bird community was recorded using point count method with a distant between points 50 m and a fix radius of 25 m in each point for 10 minutes observation. Observation points were placed in each of edge and interior habitat of Cocos nucifera plantation and Syzygium cumini plantation. Arthropod sampling was done twice using yellow trap. High bird abundance and richness were recorded in edge habitat. A total of 24 bird species of 18 families and 10 orders of arthropod were identified in the study plots. There is no correlation between arthropod and bird abundance. Based on major diet, 46% of bird species were insectivores, while 54% species where other types of eater such as 29% species were frugivores, 9% species were nectarivores, and each 4% of bird species were seabirds, carnivores and scavengers, omnivores, and other bird groups). Key words: arthropod communities, bird communities, fragmentation, Ternate